2020
DOI: 10.1093/gerona/glaa008
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Physical and Cognitive Performance Among Community-Dwelling Older Adults in Switzerland

Abstract: Background With population aging, a key question is whether new cohorts of older people are in better health than previous ones. This study aimed to compare the physical and cognitive performance of community-dwelling older adults assessed at similar age in 2005, 2010, and 2015. Methods This repeated cross-sectional analysis used data from the Lausanne cohort 65+, a three random sample population-based study. Performance of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…Previous analyses of Lc65þ data showed that all timed tests improved over time across cohorts of individuals born before, during, and at the end of World War II. 29 This appears in current analyses showing higher mean times in our study sample for the longer-term analyses that included only the first Lc65þ cohort, with participants born before the war. Although the 14-year mortality analysis was limited to individuals of the first cohort, associations found in this subsample were consistent with shorter-term observations.…”
Section: Discussionmentioning
confidence: 65%
“…Previous analyses of Lc65þ data showed that all timed tests improved over time across cohorts of individuals born before, during, and at the end of World War II. 29 This appears in current analyses showing higher mean times in our study sample for the longer-term analyses that included only the first Lc65þ cohort, with participants born before the war. Although the 14-year mortality analysis was limited to individuals of the first cohort, associations found in this subsample were consistent with shorter-term observations.…”
Section: Discussionmentioning
confidence: 65%
“…Three additional articles [11][12][13] were identified from backward citation tracing and one [14] from a conference abstract; this making a total of 17 papers. On final inspection, five studies [12,[15][16][17][18] used data from the Chinese Longitudinal Healthy Longevity Survey; three [15,17,18] were retained as they contained non-overlapping results and two [12,16] [11,15,17,18]), followed by the USA (n=4 [14,[20][21][22]) and Sweden (n=3 [8,19,23] studies), with one study each from Denmark [24], France [25], Switzerland [26] and the UK [13] (Table 1). Eight studies [8,13,15,17,18,20,23,24] were nationally representative and three studies [14,25,26] were regionally representative.…”
Section: Resultsmentioning
confidence: 99%
“…On final inspection, five studies [12,[15][16][17][18] used data from the Chinese Longitudinal Healthy Longevity Survey; three [15,17,18] were retained as they contained non-overlapping results and two [12,16] [11,15,17,18]), followed by the USA (n=4 [14,[20][21][22]) and Sweden (n=3 [8,19,23] studies), with one study each from Denmark [24], France [25], Switzerland [26] and the UK [13] (Table 1). Eight studies [8,13,15,17,18,20,23,24] were nationally representative and three studies [14,25,26] were regionally representative. Seven studies [8,12,14,18,[23][24][25] focused on the very-old (e.g., age ≥70 years) with the remaining studies capturing people aged ≥60 years.…”
Section: Resultsmentioning
confidence: 99%
“… 19 However, diverging trends still arose from objective health assessments. 20 Whereas Baby Boomers achieved the highest physical performance levels (e.g. gait speed, timed up and go), they performed worse in cognitive tests (e.g.…”
Section: What Has It Found?mentioning
confidence: 99%